Theta-burst transcranial magnetic stimulation to the prefrontal cortex impairs metacognitive visual awareness. - Rounis, E; Maniscalco, B; Rothwell, J; Passingham, R; Lau, H (2010)
We used a recently developed protocol of transcranial magnetic stimulation (TMS), theta-burst stimulation, to bilaterally depress activity in the dorsolateral prefrontal cortex as subjects performed a visual discrimination task. We found that TMS impaired subjects' ability to discriminate between correct and incorrect stimulus judgments. Specifically, after TMS subjects reported lower visibility levels for correctly identified stimuli, as if they were less fully aware of the quality of their visual information processing. A signal detection theory analysis confirmed that the results reflect a change in metacognitive sensitivity, not just response bias. The effect was specific to metacognition; TMS did not change stimulus discrimination performance, ruling out alternative explanations such as TMS impairing visual attention. Together these results suggest that activations in the prefrontal cortex in brain imaging experiments on visual awareness are not epiphenomena, but rather may reflect a critical metacognitive process.